Design and synthesis of novel quinazolinone-based derivatives as EGFR inhibitors with antitumor activity - Amr Sonousi; Rasha A. Hassan; Eman O. Osman; Amr M. Abdou; Soha H. Emam (Taylor & Francis Group, 2022)
Nineteen new quinazolin-4(3H)-one derivatives 3a-g and 6a-l were designed and synthesised to inhibit EGFR. The antiproliferative activity of the synthesised compounds was tested in vitro against 60 different human cell lines. The most potent compound 6d displayed superior sub-micromolar antiproliferative activity towards NSC lung cancer cell line NCI-H460 with GI50 = 0.789 µM. It also showed potent cytostatic activity against 40 different cancer cell lines (TGI range: 2.59-9.55 µM). Compound 6d potently inhibited EGFR with IC50 = 0.069 ± 0.004 µM in comparison to erlotinib with IC50 value of 0.045 ± 0.003 µM. Compound 6d showed 16.74-fold increase in total apoptosis and caused cell cycle arrest at G1/S phase in breast cancer HS 578T cell line. Moreover, the most potent derivatives were docked into the EGFR active site to determine their binding mode and confirm their ability to satisfy the pharmacophoric features required for EGFR inhibition.